Eating smart: Free-ranging dogs follow an optimal foraging strategy while scavenging in groups - Sarkar, Rohan; Bhowmick, Anirban; Dasgupta, Debsruti; Banerjee, Rounak; Chakraborty, Poushali; Nayek, Abhijit; Sreelekshmi, R.; Roy, Aritra; Sonowal, Rituparna; Mondal, Amartya Baran; Bhadra, Anindita (Frontiers in Ecology and Evolution, 2023)
Foraging and acquiring of food is a delicate balance between managing the costs (both energy and social) and individual preferences. Previous research on solitarily foraging free-ranging dogs showed that they prioritise the nutritionally highest valued food, but do not ignore other less valuable food either, displaying typical scavenger behaviour. We conducted a similar experiment on 136 groups of dogs with the same set-up to see the change in foraging strategies, if any, under the influence of social cost like intra-group competition. We found multiple differences between the strategies of dogs foraging alone versus in groups with competition playing an implicit role in the dogs’ decision making when foraging in groups. Dogs continually assessed and evaluated the available resources in a “patch,” transitioning from random foraging to systematic foraging with time and more information. Dogs in groups used an, “eat first, sample afterwards” strategy whereas individual dogs sampled thoroughly before eating. Additionally, dogs in groups were quicker and more likely to respond to the experimental set-up and eat from it. The dogs adjusted their behaviour in terms of effort and time allocated according to the quality of the “patch.” Foraging in groups also provided benefits of reduced individual vigilance. The various decisions and choices made lend support to the optimal foraging theory wherein the dogs harvested the nutritionally richest patch possible with the least risk and cost involved but were willing to compromise if that was not possible. This underscores the cognitive, quick decision-making abilities and adaptable behaviour of these dogs, which is likely to have influenced the process of dog domestication.